A backbone-based flow cytometry approach to decipher regulatory T cell trajectories in the human thymus - Beatriz Moleirinho; Beatriz Moleirinho; Margarida Paulo-Pedro; Margarida Paulo-Pedro; Nicole C. Martins; Nicole C. Martins; Emily Jelagat; Emily Jelagat; Eller Conti; Eller Conti; Tiago R. Velho; Tiago R. Velho; et al. (Frontiers in Immunology)
Thymus-committed regulatory T cells (Tregs) are essential for immune homeostasis. Recent findings stress their heterogeneity, suggesting possible alternate routes for thymic Treg development with unique features in humans, namely the clear evidence of Treg commitment at the double-positive (DP) stage and the presence of a significant population of CD8 single-positive (SP) FOXP3pos Tregs. Here, we present a dedicated analysis strategy to a spectral flow cytometry-based study of thymus from children and aged adults (≥ 74-years-old), to further elucidate Treg development and heterogeneity in the human thymus. We applied an unsupervised analysis pipeline to data generated from 6 high-dimensional panels, taking advantage of a common backbone of 11 markers, and we were able to map thymocytes along T cell maturation stages. Generating UMAP and FlowSOM cluster coordinates from the backbone, we projected all other markers onto these, characterizing clusters with the information of all markers. Focusing this analysis on events inside a putative total Treg gate, we could portray rarer subsets of human thymic Tregs and investigate their trajectories using pseudotime analysis. We uncover clusters within human DP thymocytes uniquely expressing FOXP3 or CD25, a DP-branching trajectory towards a CD103posCD8SP Tregs endpoint, and define trajectories towards CD4SP Tregs, including towards a cluster of CXCR3posCD4SP Tregs, that may consist of thymic resident or recirculating Tregs, and do not expand in the elderly. Our flow cytometry approach separates Treg populations with likely distinct functions and facilitates the design of future studies to unravel the complexity of human regulatory T cells.